Tinjauan Etika Bisnis Islam dan Undang-Undang Perlindungan Konsumen Terhadap Penggunaan Alat Produksi Cincau - Aldana, Lavia Vega (Institut Agama Islam Negeri Ponorogo, 2021)
Islamic business ethics are several ethical business behaviors (akhlaq al-Islamiyah) wrapped in shari'ah provisions. Currently, some producers have not met the principles of Islamic business ethics, as in the practice of black grass jelly production in Jatisari Village, Geger District, Madiun Regency, which still uses cooking utensils that do not meet standards. This study aims to analyze how grass jelly production tools are used when viewed with Islamic business ethics and Law Number 8 of 1999 concerning Consumer Protection. The type of research used in this research is field research using qualitative methods. The results of this study are; in terms of Islamic business ethics, the cooking/production utensils used in the production of black grass jelly in Jatisari Village, Geger District, Madiun Regency are following Islamic business ethics principles. However, these tools do not follow the Consumer Protection Act, namely in Article 4 paragraph (1) and paragraph (3) concerning consumer rights. The implications of this research are expected to provide input to improve the application of Islamic business ethics and the rules of Law Number 8 of 1999 concerning Consumer Protection for Cincau producers.